Disintegration of Law and Morality in the Substance of Legislation: Between Legal Sovereignty and Popular Sovereignty in the Construction of Nation Law - Andika Adhyaksa; Sudaryanto Sudaryanto; Sri Indriyani Umra (JATISWARA, 2026)
This research examines the relationship between law, morality, and power in Indonesia's democratic rule of law state, focusing on the practice of legislation formation and enforcement. Stemming from normative concerns over law's increasing instrumentalization as a political tool that distances itself from moral values and public needs, this study employs a juridical-normative method with conceptual and philosophical approaches. Guided by three research questions concerning the theoretical manifestation of law-morality-power relations, the tensions between formal legality and moral legitimacy in contemporary legal products, and strategic measures to reconstruct their interconnection this analysis critically examines the Job Creation Law, the new Criminal Code, and the amendment to the Indonesian National Armed Forces Law as concrete cases illustrating the gap between legal formality and moral substance. The findings reveal that weak interconnection between law and morality has eroded public trust in legal institutions. Legislation formation dominated by political interests and minimal public participation tends to produce unresponsive and inequitable regulations. This study recommends three strategic measures: transparent and participatory legislative processes based on social impact and human rights analysis, substantive legal balance between state interests and citizen protection, and strengthened oversight of power through independent institutions, press freedom, and civil society participation. These measures are essential for realizing meaningful law that serves social welfare within a democratic rule of law framework.